Cost-Benefit Analysis of Three-Dimensional Craniofacial Models for Midfacial Distraction: a Pilot Study. (September 2017) - Rogers-Vizena, Carolyn R.; Flath Sporn, Susan; Daniels, Kimberly M.; Padwa, Bonnie L.; Weinstock, Peter
Objective: Patient-specific three-dimensional (3D) models are increasingly used to virtually plan rare surgical procedures, providing opportunity for preoperative preparation, better understanding of individual anatomy, and implant prefabrication. The purpose of this study was to assess the benefit of 3D models related to patient safety, operative time, and cost. Design: Retrospective review. Setting: Academic, tertiary care hospital. Patients, Participants: Midfacial distraction was studied as a representative craniofacial operation. A consecutive series of 29 patients who underwent a single type of midfacial distraction was included. Intervention: For a subset of patients, computed tomography-derived 3D models were used to study patient-specific anatomy and precontour hardware. Main Outcome Measures: Complications, operative time, blood loss, and estimated cost. Results: Twenty patients underwent midfacial distraction without and nine with preoperative use of a 3D model. Seven complications occurred in six patients without model use, including premature consolidation (3), cerebrospinal fluid leak (2), and hardware malfunction (2). No complications were reported in the model group. Controlling for surgeon variation, model use resulted in a 31.3-minute (7.8%) reduction in operative time. Time-based cost savings were estimated to be 1036. Conclusions: Three-dimensional models are valuable for preoperative planning and hardware precontouring in craniofacial surgery, with potential positive effects on complications and operative time. Savings related to operative time and complications may offset much of the cost of the model.